Enhanced singlet oxygen generation of zinc and indium phthalocyanines when conjugated to cysteine functionalized graphene quantum dots - Atmaca, Goknur Yas; Sabbagh, Nazeer Kheer; Celep, Kevser; Sen, Pinar; Sahin, Fikrettin; Erdogmus, Ali (ELSEVIER, 2025)
The aim of this study is to introduce two new innovative metal phthalocyanines (Pcs); zinc phthalocyanine and indium phthalocyanine, with bromo substituent to use in non invasive approaches for cancer therapy. These approaches include photochemical and sono-photochemical studies in which the generation of singlet oxygen was tested. Halogen substituents are commonly incorporated into phthalocyanine photosensitizers due to the heavy atom effect, where the presence of heavier halogens enhances intersystem crossing (ISC) which leads to a higher yield of triplet-state formation, thereby improving the photosensitizer's efficiency in generating reactive oxygen species. For this purpose, the synthesis of 2-bromo-4-methylphenol tetra-substituted zinc and indium phthalocyanines was carried out. The obtained new phthalocyanine derivatives were conjugated to cysteine functionalized graphene quantum dots (cys-GQDs) to form supramolecular hybrids through it-it stacking. The photophysical-chemical and sono-photochemical properties of zinc and indium phthalocyanines alone and Pc-conjugated to the GQD nanomaterial were investigated in solutions. All samples demonstrated singlet oxygen generation, with the conjugated complexes showing enhanced production, as observed through the photochemical method. However, the singlet quantum yields produced by the conjugated complexes decreased with sono-photochemical methods compared to the Pcs alone which might be attributed to the possible formation of the non-sono-luminescence sensitive fragments. This study contributes to literature in understanding singlet oxygen generation behavior of conjugated phthalocyanines.
Keywords: Zinc phthalocyanine; Indium phthalocyanine; Sono-photochemical; Photosensitizer; Singlet Oxygen; Graphene Quantum Dot; SONODYNAMIC THERAPY; FLUORESCENCE BEHAVIOR; RECENT PROGRESS; CANCER-THERAPY; EFFICACY; ULTRASOUND; STATES; Chemistry